Moral Values of the Main Character in Jennifer Lee’s Wish (2023) - Apsari, Ni Made Cintya Dwi; Suarniti, Gusti Ayu Made Rai (Yayasan Sembilan Pemuda Indonesia, 2025)
This study identifies the moral values embodied by the main character in the script of Wish (2023), a movie written by Jennifer Lee. The research applies the theoretical framework of Linda and Richard Eyre’s Teaching Your Children Values (1993), supported by Carol K. Sigelman and David R. Shaffer’s Life Span Human Development (1995). A qualitative descriptive method was employed, with the movie script serving as the primary data source. Data were collected through repeated readings and note-taking techniques to extract dialogues reflecting moral values. The analysis reveals that the main character exhibits 12 distinct moral values, categorized into two groups: values of being honesty, courage, peaceability, self-reliance and potential, self-discipline and moderation, fidelity and chastity and values of giving loyalty and dependability, respect, love, unselfishness and sensitivity, kindness and friendliness, and justice and mercy. These values collectively reflect the character’s inner integrity and outward compassion, demonstrating the importance of both personal growth and social harmony. The study’s novelty lies in its focused analysis of a contemporary animated film through the lens of established moral education theory. Practically, it emphasizes how animated narratives can serve as effective tools for moral development, especially in younger audiences. The study contributes to the field of literary and film analysis by highlighting the social impact of cinematic storytelling in promoting ethical behavior and community-mindedness.